Analysis of Customer Loyalty Influenced by E-Service Quality and Promotion through Consumer Satisfaction as Mediation Variable - Yulihapsari, Ika Utami; Indrawan, Rully; Simarmata, Juliater; Zainal, Munawaroh (Yayasan Sinergi Kawula Muda, 2025)
This study aims to analyze the effect of E-Service Quality and Promotion on consumer loyalty, with consumer satisfaction as a mediating variable. In January 2024, a survey was conducted on 105 respondents based on TopBrand survey data. This survey was used to test the validity and reliability of the instrument and test the hypothesis to identify direct and indirect influences between the research variables. The results of the study indicate that E-Service Quality and Promotion have a direct influence on consumer satisfaction and loyalty. In addition, E-Service Quality and Promotion indirectly affect consumer loyalty through consumer satisfaction. The practical implications of these findings emphasize that efforts to improve service quality and positive promotional strategies can be a strategic step in increasing consumer satisfaction, ultimately contributing to customer loyalty. The findings of this study provide strategic insights for companies, especially in the technology-based service sector, such as delivery services or e-commerce. Companies need to improve the quality of electronic services by ensuring a reliable, fast, secure, and easy-to-use platform and providing responsive customer service.